Strategi Penyelesaian Pembiayaan Murābah}Ah Bermasalah Di Bmt Muamalat Jumapolo Karanganyar - Putra, Achmad Buchori Syah, Nurul Huda, M.Ag (2017)
Murābahah financing is the sale of goods by stating the acquisition price and profit agreed by sellers and buyers. This study aims to describe the strategy that is used as financing completion of murābah}ah problem in BMT Muamalat of Jumapolo and to describe the suitability of problem-solving strategies of murābah}ah financing in BMT Muamalat of Jumapolo with the decision of the National Islamic Council (DSN) of Majelis Ulama Indonesia (MUI) No. 47 / DSN-MUI / II / 2005 and No. 04 / DSN-MUI / IV / 2000. This research includes a field research by using qualitative analysis technique. Techniques used in collecting data are observation, interview, and documentation. Data analysis uses inductive and deductive methods. The results of this research is that the strategy used by BMT Muamalat to rescue assets by administrative policy is in accordance with collectability members, and non-litigation settlement with efforts to execute a guarantee (collateral) and perform bleaching policy, and almost the entire strategies used by BMT Muamalat in resolving troubled murābah}ah financing are in accordance with DSN MUI Fatwa No. 04 / DSN-MUI / IV / 2000 concerning murābah}ah in the decision to E and F points 1 and DSN Fatwa No: 47 / DSN-MUI / II / 2005 on Settlement of murābah}ah Receivables for Clients Not Being Able to Pay in its first decision and the first point in closing decision.